Internalization of Wasathiyyah Values in Efforts to Enhance the Religiosity and Tolerance of Students Based on Mentoring: An Exploratory Study of the UPI Tutorial Program - Udin Supriadi; Mohammad Rindu Fajar Islamy; Achmad Faqihuddin (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
This research aims to explore the efforts of internalizing the values of wasathiyyah in the endeavor to enhance religiosity and tolerance attitudes based on mentoring. Since the Indonesian government introduced the concept of religious moderation as a preventive measure to counteract radicalism in society, the majority of State Universities have sought to implement this policy through various programs on their campuses. In Indonesia, the official stance is against radical ideologies, given the potential divisive consequences and the emergence of terrorist actions. In 2016, the Setara Institute surveyed 171 schools in Jakarta and Bandung and observed that seeds of terrorist ideologies had emerged within classrooms. At the Universitas Pendidikan Indonesia, supported by the Rector, the Tutorial program was established with the aim of enhancing the individual piety of students. Using a qualitative approach, data collection combined ethnographic methods and interviews with 17 students. Data analysis followed the Miles and Huberman framework, including drawing, displaying data, reduction, and conclusion. The research findings indicate significant results, wherein the mentoring-based tutorial program with the internalization of wasathiyyah values enhances the religiosity and tolerance of students through the selection of qualified mentors, a wasathiyyah curriculum, inclusive communities, and ongoing evaluation. Collaboration with relevant parties is deemed necessary.  Keywords:  Wasathiyyah Values, Mentoring, Tolerance